Editorial - Wallace, Daniel J. (Current Rheumatology Reviews, 2007)
The issue of immunization in patients with autoimmune disease has plagued rheumatologists for over 50 years. This has been confounded by a report from the World Health Organization recommending that individuals with autoimmune diseases should not receive allergy shots. Case reports have been published demonstrating instances whereby the development of a vasculitic or inflammatory process was temporally associated with a vaccine. It is indeed possible that immune suppressed patients exposed to a child who received a live vaccine are at an increased risk of developing that infection (although no case reports have ever been published in the rheumatic disease literature). Further, many patients observe a flare of their inflammatory process after receiving routine vaccinations. This could stem from their hypervigilance, coincidence or a true reaction. It is therefore a real pleasure to give the reader the opportunity to review the article by Valesini et al. in this issue of CRR, which addresses these important issues. The authors distill the subject based on numbers of patients, level of evidence based conclusions, study design, perception and practicality. In essence, the following guidelines apply: 1. Nearly all routine vaccinations are safe. 2. Rheumatic flares occur in less than 10% and are almost always transient. 3. Increased diligence is mandated if a live vaccine is given to a patient or family member, especially if one is immune suppressed. 4. The effectiveness of any given vaccination is usually 100% of what is seen in healthy controls, but may be less. Hopefully, the mitigations and concerns articulated by rheumatologists are mitigated by the thoughtful, thorough review in this issue.